2019
DOI: 10.4171/jfg/85
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of equilibrium measures on a class of planar self-affine sets

Abstract: We study equilibrium measures (Käenmäki measures) supported on self-affine sets generated by a finite collection of diagonal and anti-diagonal matrices acting on the plane and satisfying the strong separation property. Our main result is that such measures are exact dimensional and the dimension satisfies the Ledrappier-Young formula, which gives an explicit expression for the dimension in terms of the entropy and Lyapunov exponents as well as the dimension of a coordinate projection of the measure. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Feng [7] has very recently shown that all ergodic invariant measures supported on the attractors of IFS composed of affine maps are exact dimensional and satisfy a formula in terms of the Lyapunov exponents and conditional entropies. This answered a folklore open question in the fractal community and unified previous partial results obtained in [1,10]. In the non-conformal setting, this formula for the exact dimension of μ is often called a "Ledrappier-Young formula", following the work of Ledrappier and Young on the dimension of invariant measures for C 2 diffeomorphisms on compact manifolds [13,14].…”
mentioning
confidence: 52%
See 3 more Smart Citations
“…Feng [7] has very recently shown that all ergodic invariant measures supported on the attractors of IFS composed of affine maps are exact dimensional and satisfy a formula in terms of the Lyapunov exponents and conditional entropies. This answered a folklore open question in the fractal community and unified previous partial results obtained in [1,10]. In the non-conformal setting, this formula for the exact dimension of μ is often called a "Ledrappier-Young formula", following the work of Ledrappier and Young on the dimension of invariant measures for C 2 diffeomorphisms on compact manifolds [13,14].…”
mentioning
confidence: 52%
“…Let r > 0 be sufficiently small so that k ∈ N that satisfies (27) is sufficiently large that (17) holds for ε. Then, using (10), ( 26) and (17) we get…”
Section: Lemma 44mentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown recently by D.-J. Feng in [22] that every self-affine measure is exact-dimensional; previous partial results in this direction include [3,5,26]. Let us now describe the most natural generalisation of Hutchinson's dimension formula N i=1 r s i = 1 to the affine context.…”
Section: Introductionmentioning
confidence: 99%